Utilizing collaboration within elementary schools to build advocacy for the elementary music classroom - Bentley, Rose (Kansas State University, 2024)
The lessons demonstrated within this report focus on building a collaborative learning community amongst other professional educators while integrating strategies and techniques inspired by Carl Orff and Zoltán Kodály in the elementary music classroom. I integrated strategies and techniques from the Kodály Method in the lessons as students utilized sequential learning when composing rhythmic phrases that included compound words taught by the Second-Grade team and solfege when reading onomatopoeias within a well-known children’s storybook. I integrated strategies and techniques from the Orff Schulwerk approach in the lessons as students performed on kazoo-harmonicas that they created in their Art and STEM classes and improvised on xylophones. The lessons not only helped build advocacy for music education among the collaborative communities that were created, but they also helped students grow in their abilities to create music both inside and outside of the music classroom. Throughout my time in the Master’s Program at Kansas State University, I was exposed to various methods of teaching elementary music in the Symposium and Seminar courses. Within these courses, I learned about the Orff, Kodály, Gordon, and Dalcroze methodologies. After creating my own lesson plans and participating in peer lessons that support each methodology throughout these courses, I was able to integrate new ideas and strategies from each methodology into my classroom to further support my instruction. By having a better understanding of each methodology and how they function within the elementary music classroom, I can apply strategies and techniques in my classroom that are more appropriate for my students and their needs. Another course that was influential to my growth and development as a music educator was the Improvisation and Composition in Elementary Music course. This course challenged me as an educator to ensure that I am not limiting my students and their ability to freely create music. By integrating improvisation and composition into my lessons, both my students and I have been challenged to think creatively about the music making process. Even though there were many challenges when integrating improvisation and composition into the classroom, we have also grown in our comfortability and ability to create music. Overall, the courses have helped me prepare lessons that enhance student-centered learning and allow musical creativity to blossom.
Keywords: Elementary music; Collaboration; Kodaly; Orff; Improvisation and composition; Advocacy